The clash of culture and cuisine: A qualitative exploration of cultural tensions and attitudes toward food and body in Chinese young adult women. Issue 2 (31st December 2020) - Ng, Stephanie; Liu, Yining; Gaither, Sarah; Marsan, Samuel; Zucker, Nancy
Abstract: Objective: Accumulating evidence suggests that the prevalence of eating disorders among Chinese women is a public health concern. Prior studies have drawn linkages between conflicting cultural values, identity confusion, and eating disorder symptomatology, which may be relevant for understanding the rise of eating disorders amidst China's rapid economic and sociocultural transformation. Here, we explore how women's experiences with traditional eating norms and modernizing norms of femininity may shape their food and body attitudes. Method: Chinese young adult women ( N = 34; aged 18–22 years) participated in semi‐structured interviews focusing on experiences with norms surrounding eating and ideal feminine appearance, perceived conflict between these norms, and their responses to perceived conflict. Interviews were conducted via email ( n = 27) or via Skype ( n = 7). Participants were not asked about past or present diagnoses of eating disorders. Analysis of responses was guided by the principles of thematic analysis. Results: Women reported encounters with cultural eating norms and feminine appearance norms, and described factors that motivated continued or discontinued adherence to these norms. Women reported strategies of conflict resolution, which resulted in different emotional and behavioral outcomes including eating disorder symptoms. Discussion: Women's experiences with norms surrounding eating and appearance indicate the centrality of these encounters in the formation of individual and interpersonal values. Our findings suggest the importance for clinicians to assist clients in exploring the meanings behind internalized attitudes toward food and body, and to help clients balance interpersonal and individual needs. Abstract :